Optimization of Information Literacy, Knowledge, and Training for Orang Rimba In Jambi Province - Yasir Riady; Milde Wahyu; Sri Sukatmi; Melisa Arisanty; Anton Robiansyah; Sri Maulidia Permatasari; M. Firman Karim (Yayasan Cendekiawan Digital Indonesia, 2024)
Enhancing the skills and training capabilities of the Orang Rimba in Jambi Province involves various activities such as drawing skills, information literacy, and computer skills. These activities are designed to develop individual potential and provide them with the necessary tools to adapt to the demands of the times. The main goal of this training is to improve their competence and knowledge in these fields, thereby facilitating their daily lives and future endeavors while encouraging self-reliance through the acquired knowledge. Additionally, this training aims to equip them with specific skills that can enhance their opportunities for independence and success in the future. Local experts and volunteers are actively involved in organizing this community service program. They not only share their knowledge but also provide the moral support and motivation that the participants greatly need. The results of this training have shown significant improvements in the participants' skills and knowledge, which is concrete evidence of the program's effectiveness. In conclusion, the community service program serves as an effective approach to enhancing the skills and knowledge of the Orang Rimba in various fields, helping them become more independent and prepared to face future challenges.